Six ideas that shaped physics - Moore, Thomas A. (McGraw-Hill, 2003)
Six ideas that shaped physics is the 21st century's alternative to traditional, encyclopedic textbooks. Thomas Moore designed SIX IDEAS to teach students: --to apply basic physical principles to realistic situations --to solve realistic problems --to resolve contradictions between their preconceptions and the laws of physics --to organize the ideas of physics into an integrated hierarchy